Secondary Prevention of Esophageal Variceal Bleeding Using Transjugular Intrahepatic Portosystemic Shunt Compared to Endoscopic Band Ligation plus Beta-Blocker - Yo, Edward Christopher; Nursyirwan, Saskia Aziza (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2023)
Aim: This study aims to compare the effectiveness of transjugular intrahepatic portosystemic shunt (TIPS) against combination therapy in the secondary prevention of esophageal variceal bleeding.Method: Literature search was conducted using 4 databases (PubMed, Cochrane, Ovid MEDLINE, and Ovid Embase) and individual hand searching. The selected studies were then critically appraised for their validity, importance, and applicability.Results: A total of 136 results were retrieved, and 2 systematic reviews and meta-analysis of randomized controlled trials (RCTs) were selected. Both studies showed that TIPS significantly decreased incidence of esophageal variceal rebleeding but had no significant effect on reducing overall mortality when compared to combination therapy. Study by Lin et al found that TIPS was significantly better than combination therapy for reducing mortality from variceal rebleeding, but study by Jing et al found no significant difference.Conclusion: TIPS is superior to combination therapy in reducing the incidence of esophageal variceal rebleeding. Nevertheless, its effectiveness in reducing mortality needs further investigation. Future research should look into its complications and cost-effectiveness in developing countries like Indonesia.